Disparity in Teachers’ Discernment of Malbazar & Matiali Blocks of Dooars Region of West Bengal towards Universalization of Elementary Education Gour Sundar Ghosh, Prasenjit Deb - Ghosh, Gour Sundar; Deb, Prasenjit (International Journal of Scientific Research and Management (IJSRM), 2017)
Teachers are regarded as one of the most important group of professionals for Nation building. As theteachers are directly involved in the academic, mental, physical, moral, spiritual, and psycho-socialimprovement of the children, hence it will ultimately cultivate educational system. This study conductedin Jalpaiguri, a Sarva Shiksha Mission (SSM) district of West Bengal since 2002 to estimate and reviewthe level of achievement earned by the Elementary Teachers from the SSM – its objective and purposesmethods and approaches. This study had concentrated to identify the differences of the level of perceptionabout dropout of elementary school level among the school teachers, in term of 18 variables viz. Age (X1),Education of teachers (X2), Training Experience (X3), Year of Experience (X4), Engagement in otheractivity (X5), Family Income (X6), Social Participation (X7), Interaction with Head Teacher (X8),Interaction with School Inspectors (X9), Interaction with SSM Personnel (X10), Organizational Interfacing(X11), Involvement in SSM actions (X12), Value Judgement (X13), Response about SSM activities (X14),Use of TL Materials (X15), Exposures to Media (X16), Opinion about present education system (X17), andChallenges to SSM (X18). The statistical analysis illustrated that while the variables: like (1) Education ofteachers (X2), Social Participation (X7), Interaction with Head Teacher (X8), Use of TL Materials (X15)had wielded a substantive effect on the determining level of Effectiveness of SSM (Y) and (2) variables:like Age (X1), Education of teachers (X2), Year of Experience (X4), Engagement in other activity (X5),Family Income (X6), Social Participation (X7), and Interaction with Head Teacher (X8) were found to bearmentionable impact on the high and low level of Effectiveness of SSM (Y) of the school teachers of WestBengal